Assessment of Selected Practices of Menstrual Hygiene among Rural Women at Pune City - Prachi Jadhav1 , Aman Janbandhu1 , Tushar Thorat1 , Arunya Rajan1 , Leeja Bonny Thomas2 , Sheela3 Up (Institute of Medico-legal Publications Pvt Ltd, 2020)
Menstruation: Despite the irrational taboos related to it, menstruation is a natural physiological method thateach healthy girl undergoes. Though every girl experiences it on a regular basis, not everyone seems tobe intelligent about the necessity to confirm hygiene. Menstruating girls ought to pay explicit attention toprivate hygiene. During this time, a woman’s vulnerability towards major ailments will increase.Poor expelling hygiene will result in several problems, such as fungal or microorganism infections ofthe reproductive tract and the urinary tract.The result shows during assessment of selected practices of menstrual hygiene among rural women 97%wash hands after changing pad, 98% women take bath during their menstruation, 38% women’s familykeeps them and their things separate during menstruation, 5% women have financial crisis/problem forbuying sanitary napkins and also 57% women avoid travelling to menstrual hygiene